Assessment of classical swine fever diagnostics and vaccine performance - Blome, S; Meindl-Böhmer, A; Loeffen, W; Thuer, B; Moennig, V (Revue scientifique et technique (International Office of Epizootics), 2006)
Rapid and accurate diagnosis is of the utmost importance in the control of epizootic diseases such as classical swine fever (CSF), and efficacious vaccination can be used as a supporting tool. While most of the recently developed CSF vaccines and diagnostic kits are mostly validated according to World Organisation for Animal Health (OIE) standards, not all of the well-established traditional vaccines and diagnostic tests were subject to these validation procedures and requirements. In this report, data were compiled on performance and validation of CSF diagnostic tests and vaccines. In addition, current strategies for differentiating infected from vaccinated animals are reviewed, as is information on the control of CSF in wildlife. Evaluation data on diagnostic tests were kindly provided by National Reference Laboratories for CSF in various European countries.